First principles investigations of rotational barrier and hyperfine interactions of muonium in tetraphenylsilane / Pek-Lan Toh ... [et al.] - Toh, Pek-Lan; Sulaiman, Shukri; Mohamed-Ibrahim, Mohamed Ismail; Jayasooriya, Upali A. (2012)
In this work, we have used the Density Functional Theory (DFT) method to study the rotational barrier for the muoniated-tetraphenylsilane, SiPh4-Mu system. Three Muonium (Mu) trapping sites were considered in the investigations, namely ortho, meta, and para positions on one of the phenyl rings. The positions of muonium (Mu) at the three different sites were determined by performing geometry optimization procedures. The geometry optimizations for all the systems were employed to calculate the local energy minima of the system as well as the hyperfine coupling constant for the Mu. The Mu-attached phenyl ring was then rotated about the Si- C bond at the intervals of 10° for a complete 360° rotation. For all three cases, the calculated energy profiles exhibited two barriers. In the case of both meta and para sites, the profiles as well as the location of the barriers were nearly the same. While for the ortho case, the positions of the two barriers differ slightly with the other two cases. The calculated barrier height for the rotation of Mu-attached phenyl ring was less than 0.8 eV.The major part of the total hyperfine coupling constants for the Mu was from isotropic component. The corresponding values vary from 372.40 MHz to 475.65 MHz. On the other hand, a very small value of anisotropic hyperfine coupling constants for the Mu was calculated.